2003
DOI: 10.1093/toxsci/kfg150
|View full text |Cite
|
Sign up to set email alerts
|

Antiandrogenic Effects of Bisphenol A and Nonylphenol on the Function of Androgen Receptor

Abstract: By using a yeast detection system for androgenic and antiandrogenic effects of chemicals, we identified bisphenol A (BPA) and nonylphenol (NP) as antiandrogens. In this study, we report molecular mechanisms for the antiandrogenic action of BPA and NP. In the ARhLBD-activating signal cointegrator 1 (ASC1) yeast two-hybrid system, which reflects the androgen-dependent interaction between androgen receptor (AR) and its coactivator, ASC1, BPA and NP acted as potent AR antagonists comparable to a known strong antag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
198
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(208 citation statements)
references
References 52 publications
8
198
0
2
Order By: Relevance
“…It also showed that BPA has adverse effects on the reproductive system in male rats. BPA is reported to have both estrogenic and antiandrogenic effects (6,23,24). Several toxicological studies (25) pointed out that rodents exposed to BPA during the prenatal or perinatal period show a large variety of adverse reproductive outcomes, including decreased epididymal weight and daily sperm production (26,27) and increased prostate weight (28), which is somewhat similar to our findings.…”
Section: Discussionsupporting
confidence: 89%
“…It also showed that BPA has adverse effects on the reproductive system in male rats. BPA is reported to have both estrogenic and antiandrogenic effects (6,23,24). Several toxicological studies (25) pointed out that rodents exposed to BPA during the prenatal or perinatal period show a large variety of adverse reproductive outcomes, including decreased epididymal weight and daily sperm production (26,27) and increased prostate weight (28), which is somewhat similar to our findings.…”
Section: Discussionsupporting
confidence: 89%
“…We used several known competitors (unlabeled DHT, BIC, and OHF) of DHT as positive controls (38,51). The IC 50 (the concentration of ligand that were able to inhibit AR-DHT binding by 50%) of DIMN was 1-2 M, while the IC 50 values of unlabeled DHT, OHF, and BIC were 1-2 nM, 0.4 -0.5 M, and 0.9 M, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Radiolabeled dihydrotestosterone ([ Plasmids-The mammalian expression plasmids of the mouse AR (pcDNA3.AR), mouse GR (pcDNA3.GR), pARE 2 -TATA-Luc, PSA-Luc, MMTV-Luc, GFP-AR, pCR3.1-SRC1, and pSG5-HA-GRIP-1 (SRC-2) have been previously described (35)(36)(37)(38)(39)(40). The pcDNA3.ER␣ (human ER␣ expression plasmid) and ERE-Luc reporter constructs were kindly provided by Dr. J. W. Lee (Baylor College of Medicine) (41).…”
Section: Methodsmentioning
confidence: 99%
“…BPA exposure has also been associated with reproductive dysfunctions, including reduction of testicular weight and sperm count, alterations of hormone levels, and impairment of spermatogenesis (Jin et al, 2013;Pacchierotti et al, 2008;Sakaue et al, 2001;Tiwari and Vanage, 2013;Wang et al, 2016). The mechanism of action of BPA has been investigated with respect to its estrogenic activity, such as effects on steroid hormone synthesis, and androgen receptor (AR) antagonism (Kitamura et al, 2005;Lee et al, 2003;Vinggaard et al, 2008;Zhang et al, 2011). Due to public concern about these potential adverse effects of BPA, the U.S. Food and Drug Administration (FDA) has enforced restrictions on the manufacture and usage of BPA (FDA, 2012(FDA, , 2013.…”
mentioning
confidence: 99%